Use of high frequency jet ventilation as a refinement for imaging macaques with respiratory disease. (August 2020) - Sharpe, Sally A; Scott, Shaun; Taylor, Irene; Skinner, Oliver; Clark, Simon O; Smyth, Donna; McIntyre, Anthony; Gleeson, Fergus V; Dennis, Mike J
Imaging is used in human medicine to diagnose disease and monitor treatment efficacy. Computed tomography (CT) positron emission tomography (PET) and magnetic resonance (MR) are applied to animal models of infectious diseases to increase data quality, enhance their relevance to the clinical situation, and to address ethical issues through reduction of numbers and refinement of study designs. The time required for collection of MR and PET-CT scans means that normal breathing produces motion artefacts that can render images unacceptable. We report, for the first time, the use of high frequency jet ventilation (HFJV) for respiratory management during imaging of macaques. HFJV enables continuous gaseous exchange, resulting in cessation of spontaneous breathing motion thus providing a motionless field without the potential stresses induced by repeated breath-hold strategies.